Efektivitas Penambahan Limbah Kotoran Sapi Dalam Pengolahan Kompos Dari Limbah Daun Jati Menggunakan EM-4 Di Desa Tuksono Kecamatan Sentolo Kabupaten Kulonprogo - Paramita Dwi Sukmawati; Dewi Wahyuningtyas (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Tuksono Village is in Sentolo District, Kulon Progo Regency with a population of 8,560 people in 2021 and almost all Tuksono village residents have teak plantations of around 100 hectares. Large teak plantations produce dry teak leaf waste, this is because the adaptation of teak trees in the summer is to shed their leaves. So teak leaf waste is produced every dry season and causes problems for the surrounding environment. With these problems, efforts are needed to process teak leaf waste and based on the composition of teak leaves, it can be processed into compost. In the process of composting teak leaf waste with the addition of cow dung, the C, N and C/N ratios still do not meet SNI 19.7020-2004. This is because teak leaves have a relatively high carbon content, so for the composting process of teak leaves it is not enough to just add cow dung but requires additional materials that can increase the nitrogen content such as urea or banana stem waste. The most optimal composting results are obtained from comparing the composition of teak leaf waste and cow dung from 400 g of teak leaf waste: 100 g.